UNDERSTANDING HOW JOB STRESS, ACHIEVEMENT MOTIVATION, WORK DISCIPLINE, AND EMOTIONAL INTELLIGENCE IMPACT EMPLOYEE JOB SATISFACTION - Safrida, Safrida; Wasesa, Supar; Yudha, Tri Kartika; Simbolon, Ramadona (Faculty of Economic and Business, University of Pasundan, 2023)
This research aims to explain the Job Stress, Achievement Motivation, Work Discipline and Emotional Intelligence on Employee Job Satisfaction at PT. Bank Maybank Indonesia Tbk. Diponegoro Center. A quantitative study using a saturation sample methodology was conducted on 56 employees, and multiple linear regression analysis and SEM PLS were used for data analysis. The results indicated that both emotional intelligence and job stress have an effect on job satisfaction, partially showing the same results, i.e., emotional intelligence partially has a positive and significant influence on job satisfaction and job stress has a positive and significant influence on job satisfaction. Using SEM-PLS produces the same result: emotional intelligence has a positive and significant influence on job satisfaction. Research results can be a company's input to improve performance with variables in research. Research only at PT. MayBank Indonesia Therefore, the data collected is limited to only one company.